THE INFLUENCE OF DIGITAL PROMOTION AND ONLINE MARKETING COMMUNICATION ON ADOLESCENTS’ CONSUMPTIVE BEHAVIOR IN KOTO MAJIDIN VILLAGE - Rosadi, Dea; Bustami, Alex Wissalam; Fauzi, Muhammad (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
The development of digital technology has significantly changed adolescents’ consumption patterns through exposure to social media such as Instagram, TikTok, and e-commerce platforms. This study aims to analyze the influence of digital promotion and online marketing communication on adolescents’ consumptive behavior in Koto Majidin Village. This research employs a quantitative approach using a purposive sampling technique involving 80 respondents aged 15–20 years. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that, partially, digital promotion does not have a significant effect on adolescents’ consumptive behavior, while online marketing communication has a positive and significant effect. Simultaneously, both variables significantly influence adolescents’ consumptive behavior. The coefficient of determination indicates that the model explains 80.5% of the variation in adolescents’ consumptive behavior. These findings indicate that online marketing communication is a more dominant factor in influencing adolescents’ consumptive behavior than digital promotion. This study is expected to contribute to the development of digital marketing studies and serve as a consideration in improving adolescents’ consumption literacy in the digital era.